Voter Mobilisation and Trust in Electoral Institutions: Evidence from Kenya. Issue 638 (6th April 2021) - Marx, Benjamin; Pons, Vincent; Suri, Tavneet
Abstract: In a large-scale randomised experiment implemented with Kenya's Electoral Commission, text messages intended to mobilise voters boosted electoral participation. However, the messages also decreased trust in electoral institutions after the election. This decrease was stronger for individuals on the losing side and in areas that experienced election-related violence. We hypothesise that the mobilisation campaign backfired because the Electoral Commission promised a transparent and orderly electoral process but failed to deliver on these expectations. Several potential mechanisms account for the intervention's unexpected effects, including a simple model where signalling capacity via mobilisation messages can negatively affect beliefs about election fairness.